The role of working mothers in children’s health during the covid-19 pandemic in Indonesia - Nur Asrofi, Dien Amalina; Al Ayyubi, Muhammad Salahudin (Jurnal Ekonomi Indonesia, 2025)
During the Covid-19 pandemic, apart from adult health, children's healthrequires significant attention. Governmental policies aimed at mitigating thespread of the pandemic have inadvertently restricted children's activities,adversely impacting their health. In Indonesia, many mothers have enteredthe workforce to support their families' health. This study examines the impactof working mother on children's health during the pandemic in Indonesia.Employing logit regression analysis and utilizing microdata from the 2020Socio-Economic Survey (SUSENAS), the findings suggest that workingmother has the potential to enhance children's health outcomes. Additionally,the health of children is influenced by various sociodemographiccharacteristics of the mother, including her educational attainment, type ofemployment, age, place of residence, involvement in the agricultural sector.The implications of this research highlight the pivotal role of maternalparticipation in the labor market in sustaining children's health in Indonesia.